(3JYdjb ef cJGH GdbjUQGfi aj de GdMcGes - (3eLghds; (3GdbjUQGfjs
(3ChdgG (B:s
(3hHYO aEfi hLOJ ajeG YHQ dfG Yf GdChdjf ajeG ChOYJ cJHgG ef SQgG Gdecfhf s
(3BNQgG (B:s
(3hCf jchf gh GdOGaY NjQ ef Cf jchf gh GdeOahY Edjg s
(3Vef eLehY , JQJjHgG (B: (3GdKGfjs
(3GNJjGQ ef GdLRA GdChd ef cJGH GdbjUQGfis
(3HgG fXGe GdJYbjHIs
(3ajg VHW s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs